Burnt by the Sun of International Administrative Law: A Sketch of a Legal Chameleon - Handrlica, Jakub (P.A. Persona e Amministrazione, 2022)
In 1906, D. Donati presented his thesis on existence of two particular subdisciplines of public law: administrative international law (diritto internazionale amministrativo) and international administrative law (diritto amministrativo internazionale). Here, D. Donati followed a dualistic approach, arguing for a strict distinction between public international law and municipal law. So, he understood administrative international law as an integral part of public international law and international administrative law as an integral part of municipal law. This article aims to address the reception of Donatiʼs thesis on existence of international administrative law (diritto amministrativo internazionale) in the subsequent scholarship of public law. It argues that while the term itself has been used in various jurisdictions for several decades, the scholarship has never reached any common understanding on what international administrative law actually is and where it belongs. Consequently, several different understandings if the term “international administrative law” have emerged in various jurisdictions. This article argues that absence of this common understanding is not given by differences in legal problems, but rather has been a product of an isolationistic approach of scholarship to this field of law, which hasn’t provided for a common understanding of this academic discipline. Further, this article also argues that despite a common position, the emergence of this branch of law in various jurisdictions demonstrates that international administrative law represents a part of an ius publicum europaeum.